The Influence of Work Environment and Employee Placement on Employee Performance through Job Satisfaction at the West Bekasi Pratama Tax Service Office - Fransiskus Simorangkir; Eddy Sanusi Silitonga; Irawan Noor (Dinasti Publisher, 2026)
This study aims to determine and analyze the influence of 1) the work environment on job satisfaction, 2) employee placement on job satisfaction, 3) the work environment on employee performance, 4) employee placement on employee performance, 5) the work environment on employee performance, 6) the work environment on employee performance through job satisfaction, and 7) employee placement on employee performance through job satisfaction. The study was conducted at the West Bekasi Pratama Tax Service Office with a sample of 92 respondents. The sampling technique used was saturated sampling. The data analysis methods used descriptive analysis and path analysis. The results of the study indicate that: 1) the work environment has a positive and significant effect on job satisfaction, 2) employee placement has a positive and significant effect on job satisfaction, 3) the work environment has a positive and significant effect on employee performance, 4) employee placement has a positive and significant effect on employee performance, 5) the work environment has a positive and significant effect on employee performance, 6). job satisfaction does not mediate the work environment on employee performance, and 7). job satisfaction does not mediate employee placement on employee performance